2022
DOI: 10.1111/1365-2435.14032
|View full text |Cite
|
Sign up to set email alerts
|

Moderate climate warming scenarios during embryonic and post‐embryonic stages benefit a cold‐climate lizard

Abstract: Warming temperatures caused by climate change are predicted to vary temporally and spatially. For mid‐ and high‐latitude reptiles, the seasonal variation in warming temperatures experienced by embryos and hatchlings may determine offspring fitness, yet this has remained largely unexplored. To evaluate the independent and interactive influence of seasonal variation in warming temperatures on embryonic and hatchling development, we incubated eggs and reared hatchlings of a cold‐climate oviparous ectothermic spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 135 publications
(167 reference statements)
3
24
2
Order By: Relevance
“…latitudinal or altitudinal) variations in species vulnerabilities to climate warming, our study highlights the importance of assessing species vulnerability at a local scale using high-resolution climate data and species traits to fully evaluate the biological impact of warming. Previous research predicted temperate lizards would be at lower risk of climate warming than tropical species, because temperate species are exposed to temperatures well below their thermal optima, and thus may be at reduced risk, or even benefit from increasing temperatures [4,14,94]. By contrast, we found that temperate lizards would be also highly vulnerable to warming because of increased water loss and rise of heat stress by extreme high temperature under climate warming.…”
Section: Discussioncontrasting
confidence: 52%
“…latitudinal or altitudinal) variations in species vulnerabilities to climate warming, our study highlights the importance of assessing species vulnerability at a local scale using high-resolution climate data and species traits to fully evaluate the biological impact of warming. Previous research predicted temperate lizards would be at lower risk of climate warming than tropical species, because temperate species are exposed to temperatures well below their thermal optima, and thus may be at reduced risk, or even benefit from increasing temperatures [4,14,94]. By contrast, we found that temperate lizards would be also highly vulnerable to warming because of increased water loss and rise of heat stress by extreme high temperature under climate warming.…”
Section: Discussioncontrasting
confidence: 52%
“…Ectotherms are sensitive to seasonal variations in environmental temperature (Taylor et al, 2020;Liu et al, 2022). In particular, tropical ectotherms already live in temperatures close to their optimum physiological levels (Deutsch et al, 2008).…”
Section: Editorial On the Research Topic Ecophysiological Analysis Of...mentioning
confidence: 99%
“…Lizards from medium and high latitudes could respond to thermal variation through multiple levels of metabolic acclimation, whereas their congeners from low latitudes lacked any level of modification and are thus more vulnerable to global warming (Sun et al, 2022). Embryonic and hatchling development can be improved by moderate warming in Lacerta agilis from the low-latitude margin population of a high-altitude species (Cui et al), and moderate warming benefits hatchling fitness in the cold-climate lizard, Takydromus amurensis (Liu et al, 2022). In tropical regions, species with limited dispersal abilities, small geographic ranges, and restrictions to high altitudes are particularly vulnerable to extinction (Huey et al, 2012).…”
Section: Editorial On the Research Topic Ecophysiological Analysis Of...mentioning
confidence: 99%
“…Previous studies on P. sinensis (Hebei, 39°58′N) and M. mutica (Zhejiang, 30°46′N) have been conducted on turtles from high latitudes (Zhang et al, 2019;Li et al, 2021). As it may be that high-latitude reptiles live at temperatures lower than their physiological optimum (Hao et al, 2020;Liu et al, 2022), higher environmental temperatures would be beneficial for their functions (Huey et al, 2009), and heat waves may not lead to significant oxidative damage. Similarly, in the present study, the MDA content of high latitude specimens did not increase after exposure to heat waves.…”
Section: Higher Oxidative Damage By Heat Waves In Low-latitude Turtlesmentioning
confidence: 99%